MENINGKATKAN KETERAMPILAN BERHITUNG PENJUMLAHAN BILANGAN BULAT MENGGUNAKAN MEDIA MANIK-MANIK PADA SISWA KELAS I SD INPRES TALABORONG KEC. BAJENG BARAT KAB. GOWA - Salmiati Muis; Muhammad Muzaini; Sri Satriani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to improve numeracy skills using beads in class I SD Inpres Talaborong Kec. Bajeng Barat Kab. Gowa. The type of research used in this research is Classroom Action Research (CAR). The subjects in this study were first grade students of SD Inpres Talaborong Kec. Bajeng Barat Kab. Gowa, totaling 21 students. This research was conducted in 2 (two) cycles and each cycle was carried out in three meetings outside the final test of each cycle. The data collection used is observation and tests. The results showed that in the first cycle the average score of the students as a whole was 63.3. This shows that the numeracy skills of the first graders of SD Inpres Talaborong Kec. Bajeng Barat Kab. Gowa is still relatively low. Therefore the researcher made a contribution by applying the bead media in learning and giving the media to each group so that students more easily understood how to learn to count integers. After applying the media, there was an increase in cycle II which obtained an overall average student score of 95.7. Based on these results it can be concluded that the use of media beads can improve the numeracy skills of the first graders of SD Inpres Talaborong Kec. Bajeng Barat Kab. Gowa.